Spectroscopically labelled hydroxylamino-triazine (BHT) siderophores toward the quantification of iron(III), vanadium(V) and uranium(VI) hard metal ions - Drouza, Chryssoula; Amoiridis, Angelos; Papanikolaou, Michael G.; Kabanos, Themistoklis A.; Keramidas, Anastasios D. (My University, 2024)
Based on the strong binding properties of hydroxylamino-1,3,5-triazine (BHT) for hard metal ions, a novel spectroscopically labelled triazine-hydroxylaminato ligand, N,N′-(6-(9H-carbazol-9-yl)-1,3,5-triazine-2,4-diyl)bis(N-methylhydroxylamine) (H2cbht), was synthesized. Reaction of H2cbht with FeIII, VV and UVI resulted in the synthesis of [UVIO2(cbht)(DMF)(MeOH)], 1, (PPh4)2([UVIO2(Hcbht)2]·2[UVIO2(Hcbht)(cbht)]), 2, (PPh4)2[(UVIO2)3(μ-cbht)2(cbht)2], 3, Na[VVO2(cbht)], 4, and (PPh4)[FeIII(cbht)2], 5. The complexes were characterized by X-ray crystallography showing strong chelation of the metal ions with the BHT chelating moiety H2cbht. The DMSO/DMF solutions of the complexes were characterized by NMR, UV-vis and electrochemistry, confirming the high affinity of H2cbht for FeIII, VV or UVI. The luminescence properties of the carbazole group were retained in the BHT adduct of the H2cbht ligand. Interaction of the metal ions with H2cbht resulted in quenching of the luminescence of H2cbht. Stern–Volmer plots of luminescence vs. concentration of the metal ions are linear and suitable for the determination of the concentration of metal ions in nM range concentrations. Benesi–Hildebrand plots show that the metal-to-ligand ratio is 1 : 1 while the formation of the metal complexes exhibits high association constants.